Força muscular e capacidade de exercício em pacientes hospitalizados: uma análise transversal das populações DPOC exacerbada versus insuficiência cardíaca descompensada - Peixoto, Mariana Fernandes (2024)
Chronic respiratory and cardiovascular diseases impose a significant burden on healthcare systems and economies, sharing risk factors and control measures. Both conditions involve muscular strength impairment, yet comparative evidence on the magnitude of this impairment is scarce. Therefore, understanding the impact of muscle weakness on exacerbations of chronic obstructive pulmonary disease (ECOPD) and decompensated heart failure (DHF) is essential for clinical practice, potentially optimizing care and improving functional outcomes for these patients. Objectives: To analyze whether there is a difference in peripheral muscle strength impairment and exercise capacity in hospitalized patients with exacerbations of COPD and decompensated heart failure. Additionally, we aim to assess whether muscle strength contributes to exercise intolerance in these populations. Methods: Observational, cross-sectional study including patients diagnosed with exacerbated COPD and decompensated HF, assessed between 24 and 72 hours after hospital admission. Evaluation included grip strength, quadriceps muscle strength, and exercise capacity using the 6-minute walk test (6MWT). Results: Each group consisted of 15 patients. Regarding mean grip strength, quadriceps strength, and exercise capacity, both groups showed a mean below 70% of predicted values. When analyzing the relationship between grip strength, quadriceps strength, and 6MWT distance, a high percentage of patients in both groups exhibited muscle weakness and low exercise capacity (67% in the ECOPD group and 87% in the DHF group). We observed greater variability in systolic blood pressure post-exercise, higher peak heart rate, increased dyspnea, and greater fatigue in lower limbs during exercise in the ECOPD group. There was no significant correlation between muscle strength and 6MWT distance in the ECOPD group, whereas a moderate and significant correlation was found between grip strength and 6MWT distance (R= 0.52, p = 0.04), and a strong and significant correlation between quadriceps strength and 6MWT distance (r = 0.79, p < 0.01) in the DHF group. Conclusion: Muscle strength impairment and exercise capacity are similar between COPD and HF populations during acute exacerbations. While muscle weakness may be an important factor associated with exercise capacity in DHF patients, exercise limitation in ECOPD patients appears to be influenced by more intense symptoms.